The renewable energy research contribution of Tanzania: A review - Shame, Buruhan Haji; Ubaidillah; Tjahjana, Dominicus Danardono Dwi Prija; Arifin, Zainal; Aziz, Muhammad; Harwijayanti, Widyanita; Haji, Mohammed M. (Communications in Science and Technology, 2024)
The central objectives of this study are to locate existing research on renewable energy, examine the energy policy of Tanzania, assess bibliometric factors, determine the direction of the current research, and comprehend unexplored research topics. This exploration focuses on a bibliometric-based study using computer-assisted software tools known as VOS viewer and RStudio in analyzing the Scopus data retrieved package for the key phrase of "Renewable energy" in the article titles published from 2002 to 2022. A total of 661 publications (which is only 0.45% and 6.3% of the global and continental publications from Africa respectively) were analysed after refining using different bibliometric criteria like study site, type of document, publication stage, language used in the document, and publication time interval. The results shows that Energy fuels, engineering, technology, environmental sciences, ecology, and business economics are the most frequently studied fields. Also, from a total of 661 publications, only 32 documents were published from Tanzania for 20 years from 2022 which is less than 2 publication/year. This study concludes that there is a notable lack of research output from Tanzania in this critical field. This gap underscores the need for greater investment in renewable energy research and development within the country, as well as targeted efforts to build research capacity and foster collaboration among academia, government, and industry stakeholders.